Akselerasi Literasi Perpajakan dan Pendampingan Teknis Coretax System untuk Penguatan Self-Assessment di RS Puri Raharja - I Gusti Agung Prama Yoga; Desak Rurik Pradnya Paramitha Nida; Ida I Dewa Ayu Mas Manik Sastri (Lembaga Pengabdian Kepada Masyarakat, Universitas Warmadewa, 2026)
The implementation of the Coretax Administration System (CTAS) as part of Indonesia's digital tax transformation requires taxpayers' readiness to understand the technology-based tax administration system. However, low digital tax literacy and limited technical understanding of self-assessment mechanisms remain major obstacles, especially in institutions with high work mobility, such as hospitals. This community service activity aims to increase digital tax literacy and provide technical assistance with tax reporting using the Coretax System for Puri Raharja Hospital employees. The implementation method uses a participatory empowerment approach in three stages: seminars, assistance with filling out the Coretax for personal accounts, and follow-up consultation. The implementation will be carried out at Puri Raharja Hospital, Denpasar, in March 2026. Tax literacy seminars, technical workshops, and the opening of the